On Some Pitfalls and Paradoxes of Comparative Literary Analysis (the Case Study of Anton Chekhov) - Tabachnikova, Olga (Zagadnienia Rodzajów Literackich, 2023)
The article is preoccupied by the problem of comparative analysis in the case of a writer as elusive as Chekhov, who does not formulate an open ideological message and generally withdraws his authorial voice. It raises the questions of what constitutes true kinship and similarity and highlights the vital importance of discerning above all the aesthetic aspect of the work, its poetics and artistic truth which take precedence over any structural or ideological considerations. To this end, various misconceptions and cases of false kinship are discussed, followed by examples of true continuity. In these examples, a close affinity is demonstrated through proximity of both ethics and aesthetics of the writers in question, and close textual comparisons are conducted. The next category discussed in the article addresses a paradox of simultaneously occurring rejection (or dislike) at one level, and real artistic closeness at another. We conclude by some general remarks on the nature of comparative analysis and offer another demonstration of stylistic proximity between two great writers, whose stylistics turns out to be so close that it is hard to tell them apart. We suggest that such parallels are not accidental, as form is inseparable from content, just as ethics is inseparable from aesthetics, and it is ultimately the artistic truth of the works under comparison that should always be kept strongly in focus.